FACTORS AFFECTING THE EMERGENCE AND DEVELOPMENT OF FOREIGN BORROWINGS IN ENGLISH LANGUAGE - Olimova , Matluba; G.N, Tuklieva (Scientific Impulse, 2023)
At present, English language is a predominant speaking language all over the World in regarding to other languages, because its long history English has been borrowed and took many many words and phrases from them. The top communication language lines English stays very important place there. According to Encyclopedia Britannica , the English language during the invasion, the native Britons were driven north and west into lands we now refer to as Scotland , Ireland, and Wales. In this article will investigate the emergence and development of English language by the help of foreign factors and languages.